2020
DOI: 10.1073/pnas.1920596117
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivaxspleen-dependent genes encode antigens associated with cytoadhesion and clinical protection

Abstract: Plasmodium vivax, the most widely distributed human malaria parasite, causes severe clinical syndromes despite low peripheral blood parasitemia. This conundrum is further complicated as cytoadherence in the microvasculature is still a matter of investigations. Previous reports inPlasmodium knowlesi, another parasite species shown to infect humans, demonstrated that variant genes involved in cytoadherence were dependent on the spleen for their expression. Hence, using a global transcriptional analysis of parasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…The density of PfEMP1 knobs on the RBC surface ( Figure 1B), which mediate sequestration in P. falciparum to avoid physical filtration by the spleen, was reduced fivefold upon adaptation of ex vivo isolates to in vitro culture [31]. Transcription of many P. vivax cytoadherence genes was reduced in vivo in splenectomized Aotus monkeys relative to spleen-intact monkeys, demonstrating that Plasmodium cytoadherence is likely regulated by many factors, including serum lipoproteins [16], rheology [32], and splenic pressure [33].…”
Section: The Contribution Of Rheologymentioning
confidence: 99%
“…The density of PfEMP1 knobs on the RBC surface ( Figure 1B), which mediate sequestration in P. falciparum to avoid physical filtration by the spleen, was reduced fivefold upon adaptation of ex vivo isolates to in vitro culture [31]. Transcription of many P. vivax cytoadherence genes was reduced in vivo in splenectomized Aotus monkeys relative to spleen-intact monkeys, demonstrating that Plasmodium cytoadherence is likely regulated by many factors, including serum lipoproteins [16], rheology [32], and splenic pressure [33].…”
Section: The Contribution Of Rheologymentioning
confidence: 99%
“…On the other hand, members of the TRAg gene family that were highly expressed in non-DARC Saimiri -infected P. vivax have also shown to induce antibody response in people from vivax-endemic regions. A recent study of 383 children in Papua New Guinea showed that antibodies against PvFAM-D2 were significantly more common in children with active P. vivax infections [ 159 ]. The coexpression of PvFAM-A2 and PvFAM-D2 proteins in infected reticulocytes is spleen-dependent, based on the Aotus monkey model [ 160 ].…”
Section: Humoral Immune Response Against P Vivax mentioning
confidence: 99%
“…Moreover, PVX_108770 (VIR14) of the multi-gene VIR family largely located at the subtelomeric regions also presented high sero-positivity, despite the role of its conserved globular domains in eliciting cross-reacting antibodies being unclear [ 162 , 163 ]. Other proteins, such as HYP, which is 100% conserved among P. vivax isolates from Mauritania, North Korea, India, and Brazil, and had antibodies significantly associated with protection against clinical P. vivax episodes in children [ 159 ], are a potential target of blood-stage vaccine. Taken together, it is possible that individuals with low-to-no DARC expression have lower susceptibility to infection than individuals having high DARC expression by eliciting high frequency and magnitude of anti-DBP, anti-MSP, anti-RBP, and anti-FAM antibody response against P. vivax during the blood stage.…”
Section: Humoral Immune Response Against P Vivax mentioning
confidence: 99%
“…vivax infections [156]. The coexpression of PvFAM-A2 and PvFAM-D2 proteins in infected reticulocytes is spleen-dependent based on the Aotus monkey model [157].…”
Section: Humoral Immune Response Against P Vivax and Vaccine Targetsmentioning
confidence: 99%
“…Besides, PVX_108770 (VIR14) of the multi-gene VIR family largely located at the subtelomeric regions also presented high seropositivity, despite the role of its conserved globular domains in eliciting cross-reacting antibodies is unclear [159,160]. Other proteins such as HYP that is 100% conserved among P. vivax isolates from Mauritania, North Korea, India, and Brazil, and had antibodies significantly associated with protection against clinical P. vivax episodes in children [156], a potential target of blood-stage vaccine.…”
Section: Humoral Immune Response Against P Vivax and Vaccine Targetsmentioning
confidence: 99%